PELAKSANAAN HUKUM WARIS DI MASYARAKAT KARO MUSLIM SUMATERA UTARA - Azhari Akmal Tarigan (AHKAM : Jurnal Ilmu Syariah, 2014)
Implementation of Inheritance Law of the Muslim Karo in North Sumatra. So far, Indonesia has not managed the codification and unification of a national inheritance law. Among the factors is the difficulty of codifying inheritance laws by reason of the diversity of the legal system that governs family matters of the Indonesian people, including inheritance laws. This study examines the way of implementing the inheritance law in Karo Muslim society, North Sumatra. This study focuses on the models of estate distribution to girls and widows. The article concludes that the Muslim Karo people still use customary law to resolve matters relating to inheritance disputes. Customary law that is used is experiencing dynamics or shifts. This happens without giving rise to tension let alone any disturbances within Karo Muslim community itself.DOI: 10.15408/ajis.v14i2.1279